Sex differences in congenital heart disease in Down syndrome: study data from medical records and questionnaires in a region of Japan - Takako Takano; Michio Akagi; Haruyoshi Takaki; Ryo Inuzuka; Yoshitsugu Nogimori; Hiroshi Ono; Masahide Kaneko; Norifumi Hagiwara (BMJ Publishing Group, 2019)
Reports indicate lower Down syndrome (DS) survival among females than among males in Australia, contrasting with female longevity in the general population. Using data on 1310 people with DS (626 females and 684 males) in Japan from five hospitals' medical records and questionnaires completed by parents of people with DS, we investigated sex differences in congenital heart disease (CHD), which may be related to mortality. The CHD rate was significantly higher for females (354, 57%) than for males (338, 49%; p=0.010). Significantly more females (199, 32%) than males (175, 26%) underwent surgery for CHD (p=0.018).